2019
DOI: 10.3389/fmicb.2019.02196
|View full text |Cite
|
Sign up to set email alerts
|

Saprochaete clavata Invasive Infections – A New Threat to Hematological-Oncological Patients

Abstract: BackgroundSaprochaete clavata (formerly Geotrichum clavatum, now proposed as Magnusiomyces clavatus) is a filamentous yeast-like fungus that has recently been described as an emerging pathogen mostly in patients with acute leukemia.MethodsThis is a retrospective study of patients diagnosed with proven and probable S. clavata infection at the University Hospital, Hradec Králové, Czechia between March 2005 and December 2017. Previous cases were identified from the literature and FungiScope® database.ResultsSix n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 87 publications
5
66
1
Order By: Relevance
“…Unlike other reported cases, the patient in our case had multiple myeloma, not leukemia. Due to ABMT and neutropenia, this patient was likely to be susceptible to invasive fungal infections similar to previously reported cases [ 2 , 8 - 10 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Unlike other reported cases, the patient in our case had multiple myeloma, not leukemia. Due to ABMT and neutropenia, this patient was likely to be susceptible to invasive fungal infections similar to previously reported cases [ 2 , 8 - 10 ].…”
Section: Discussionsupporting
confidence: 82%
“…In a retrospective study about S. clavata infections, Buchta et al reported colonization and IFI in 48 and 6 patients in the Hemato-Oncology Department of a teaching hospital [ 10 ]. Over the past five years, the number of S. clavata -related infections, including FungiScope™ data, has reached about 80 cases [ 4 , 10 , 13 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, time duration to adequate antifungal therapy, type of antifungal agent and surgical management were not associated with mortality. It has been reported that surgical debridement [ 7 , 29 , 30 ] and early antifungal treatment [ 31 ] may improve outcome in patients with mucormycosis [ 2 , 9 , 22 , 24 , 32 , 33 , 34 , 35 ]. The use of combination antifungal therapy did not seem to impact the survival of our patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%